Some aspects of shrimp farming systems and shrimp production management: Bangladesh perspective (Journal of Biodiversity Conservation and Bioresource Management, 2020)
Shrimp is one of the leading exportable seafood products in Bangladesh. In the 2017-2018 financial year the country has exported 36168 MT products. Present research work was conducted in three Upazilas (Kaliganj, SyamNagar and Assasuni) in Sathkira district. Three different farming practices (organic, traditional and control) were selected for the research programme. The working farmers in the farming practices were found to follow the traditional farming in the early times. Average production was found 275 kg/ha in the traditional farming practices. This is the lowest shrimp production in the world. Reasons are lack of better technology, dearth of quality seed and feed and effect of shrimp diseases. Small-scale organic shrimp farming practice was found to maintain better production and profitability in the three experimental Upazilas. Three different farming practices (viz. organic, traditional and control/ extensive farming) were taken under interview to collect data. A comparison of the production (kg/ha/yr) of three years’ time (2012 to 2014) was made for analysis in the study. The highest production rate was recorded in organic shrimp farming. It was 13.16% higher than the traditional and 15.14% higher than the control/extensive shrimp farming system. Traditional shrimp farming production was 1.98% higher than that of the control/extensive shrimp farming. Percentage of gross sell of organic system was 14.01% higher than traditional and 15.89% higher than that of the control/extensive shrimp farming. The traditional shrimp gross sell was 1.87% higher than the control shrimp. Interviews and PRA (Participatory Rural Appraisal) method were used for the collection of data. The main research question was ‘effect dose’ on the overall production, income and impact on biodiversity. Recording data showed that the organic farming practice is more sustainable and environmentally sound system. Organic farming system showed less input cost and higher production value. Organic shrimp farming system increases image value of Bangladesh in the international market.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 93-100